Pengembangan Model Pembelajaran Literasi Digital Berbasis Merdeka Belajar untuk Masyarakat Pedesaan - Eko Kuntarto (Universitas Indraprasta PGRI Jakarta, 2022)
Jambi University has a fostered village called the Integrated Laboratory Village (DLT). The DLT program is directed at developing villages as centers of economic activity that are independent and technologically minded. Thus, it is necessary to design MBKM activities carried out by Jambi University in the village so that they are in line with the goals and objectives of DLT. This study aims to develop an independent learning model (MB) targeting rural communities. The research method includes the steps of analysis and exploration, design and construction, as well as evaluation and reflection. The research subjects were 90 people. They were boarding school students, junior high school students, and village communities. The subject matter provided was Digital Literacy which was included in the Jambi University MB Curriculum scheme. The model trial was carried out by students participating in the MB program. The aspect that was tested was a set of learning models consisting of (1) learning (RPP), (2) planning materials, (3) media, (4) student worksheets, and (4) assessment instruments. The statistical calculation of the fulfillment of the indicator model showed a value of 95.5, so that the indicator was fulfilled. The validity of the procedural aspects of the model components including (1) lesson plans (RPP), (2) materials, (3) media, (4) student worksheets were valid. Based on the results of these trials, it can be said that the model is feasible to use.